Perkembangan Pasar Butik Bukittinggi (1980-2020) - Reci Stevany; Rusdi Rusdi (Jurusan Sejarah FIS UNP, 2022)
Abstract The market is a meeting place for sellers and buyers, the place is a means for sellers and buyers to carry out trade transactions in order to meet all their needs. One of the markets in Bukittinggi is a boutique market where the market sells used imported goods. This Bukittinggi boutique market began to exist around the 2000s where the traders have reached tens, of which it is estimated that 80 stalls are divided into 2 levels and the rest are selling on overhang shops or along roads that have been divided for visitors to walk. This study aims to determine the development of the boutique market in the 1980-2020 range. Therefore, researchers use qualitative methods with presenting them historical methods related to the process of tracing historical sources to producing historical facts and in the form of historical writing where heuristics, source criticism and finally interpretation are carried out. With the research results obtained, namely the development of the boutique market and the role of the local government to make the boutique market the center of the community's economy to become a place of tourism. Key word: Butik market, development, government policy